"United in Celebration" ... - Campbell, Sandy (University of Alberta Library, 2015)
This sculpture, created in 2009 by Yellowknife artist Francois Thibault depicts three drum dancers. It is located at the edge of Frame Lake in front of Yellowknife's City Hall. ...